2019
DOI: 10.1590/1517-869220192501185649
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and Static Postural Control in Volleyball Players with Transfemoral Amputation

Abstract: Introduction: A decrease in postural control and proprioception is a common result of lower limb amputation. However, postural control adaptation in Paralympic sitting volleyball players with lower limb amputation is not yet understood. Objective: The purpose of this cross-sectional controlled study was to investigate static and dynamic postural control in sitting volleyball players with unilateral transfemoral amputation. Methods: Sixteen subjects participated in the study, eight of whom were amputees with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Therefore, the aim of the present study was to analyze: (1) postural stability during single leg stance test with progressively increased balance-task difficulty in amputee soccer players compared to able-bodied soccer players; and (2) the relationship between visuomotor processing efficiency and oculomotor function to static and dynamic balance performance in amputee soccer players. In accordance with previous reports [ 1 , 10 ], it was expected that postural control in amputee soccer players may be impaired in comparison to able-bodied controls. In line with previous findings suggesting that eye movement strategies are important in balance control [ 20 , 21 , 22 ], and that visuomotor reaction time makes a significant contribution to postural stability [ 23 , 24 ], we hypothesized that high efficiency of oculomotor and visuomotor reaction will be associated with better balance control in amputee soccer players.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, the aim of the present study was to analyze: (1) postural stability during single leg stance test with progressively increased balance-task difficulty in amputee soccer players compared to able-bodied soccer players; and (2) the relationship between visuomotor processing efficiency and oculomotor function to static and dynamic balance performance in amputee soccer players. In accordance with previous reports [ 1 , 10 ], it was expected that postural control in amputee soccer players may be impaired in comparison to able-bodied controls. In line with previous findings suggesting that eye movement strategies are important in balance control [ 20 , 21 , 22 ], and that visuomotor reaction time makes a significant contribution to postural stability [ 23 , 24 ], we hypothesized that high efficiency of oculomotor and visuomotor reaction will be associated with better balance control in amputee soccer players.…”
Section: Introductionsupporting
confidence: 90%
“…On the one hand, previous studies have shown that participation in sports and/or regular physical activity has a positive effect on many aspects of amputee physical health, including cardiopulmonary, muscle strength, anaerobic power, balance and body composition [ 18 , 29 , 30 , 31 ], as well as social and psychological aspects of well-being [ 32 , 33 ]. On the other hand, it has been reported that sitting volleyball players with unilateral transfemoral amputation demonstrated poorer postural control in both static and dynamic tasks when compared to physically active non-amputees [ 1 ]. It seems that the main explanation of our study results may be the specificity of the sport activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These asymmetries are often considered to be a consequence of a pathology in which a patient compensates for movements to avoid pain or because of the desire to align the asymmetrical gait pattern [9]. According to research, the degree of gait symmetry of individuals who underwent unilateral AKA is influenced by the cause of amputation [10,11], level of physical activity [12,13] or type of prosthesis [14][15][16][17]. The key elements of the lower limb prosthesis are a well-fitted prosthetic socket and prosthetic knee joint module.…”
Section: Introductionmentioning
confidence: 99%